1987
DOI: 10.1093/nar/15.8.3581
|View full text |Cite
|
Sign up to set email alerts
|

Compilation and comparison of the sequence context around the AUG startcodons inSaccharomyces cerevisiaemRNAs

Abstract: The nucleotide sequence of the translation initiation regions of 96

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
206
1
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(216 citation statements)
references
References 23 publications
7
206
1
1
Order By: Relevance
“…The pentanucleotide upstream of the ATG in the α-tubulin genes resembles the CCACC (ATG) of verte brates [28,29], whereas a transition to the pentanucleotides of Drosophila and yeast, prefering As [9,17], is visible within the ß-tubulin genes. Pentanucleotides consisting almost completely of As are found in the other 3 macronuclear genes.…”
Section: Putative Regulatory Sequences For Initiation Of Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pentanucleotide upstream of the ATG in the α-tubulin genes resembles the CCACC (ATG) of verte brates [28,29], whereas a transition to the pentanucleotides of Drosophila and yeast, prefering As [9,17], is visible within the ß-tubulin genes. Pentanucleotides consisting almost completely of As are found in the other 3 macronuclear genes.…”
Section: Putative Regulatory Sequences For Initiation Of Translationmentioning
confidence: 99%
“…The A-residue atpos.-3 is strongly conserved in all organisms including plants and lower eukaryotes, whereas the Cs may be replaced by As, as it is found in Drosophila and yeast [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…156, [36][37][38][39][40][41][42][43][44][45][46][47][48] were isolated from a yeast YEpl3 library by screening for activity against the chromogenic aminopeptidase substrate L-leucine P-naphthylamide in intact yeast colonies. The genomic inserts were shown to contain the structural genes for aminopeptidases yscII, yscIII and ysclV.…”
mentioning
confidence: 99%
“…one following the initiating Met) was changed from Ala to Ser, and the codons for amino acids 4, 5, 11, 12 and 14 were optimized in accordance with yeast codon usage (Jansen et al, 2003). The original mammalian sequence immediately upstream of the initiator ATG was replaced with the sequence CCCGGGAAAAACAAATATAAAAAAA, designed to follow the consensus yeast translation initiation site (Hamilton et al, 1987) and to supply the XmaI site (shown in bold) for cloning.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…This result suggested that in the latter the 5 ends of the introduced Dnmt cDNAs could not efficiently drive protein synthesis in yeast cells. We therefore examined the nucleotide sequences upstream of the ATG start codon of the Dnmt1 and Dnmt3a cDNAs, comparing them with the yeast consensus translation start site (Hamilton et al, 1987). As suggested by the Western blot results, the upstream non-translated sequences of both murine genes showed no resemblance to the yeast consensus.…”
Section: Expression and Localization Of Murine Dnmt Proteins In Yeastmentioning
confidence: 99%